Hubungan Pengetahuan dan Sikap dengan Kelengkapan Antenatal Care (ANC) pada Ibu Hamil Usia Remaja - Sunajah Sunajah; Lastri Mei Winarni (Publikasi Indonesia, 2022)
Young age during pregnancy is one of the four high risks in pregnancy or known as the 4 Ts, which is too young. One of the efforts to maintain health and prevent complications in teenage pregnancy is to regularly conduct a pregnancy examination (ANC). The purpose of this study was to determine the relationship between knowledge and attitudes with completeness of antenatal care (ANC) in adolescent pregnant women. This study uses a correlational research design with a cross sectional study approach with a research sample of 189 respondents taken by total sampling technique. The results showed that the description of teenage pregnant women in the Pulomerak Health Center working area was mostly incomplete in conducting ANC visits (68.8%), most of them had good knowledge about ANC (55%) and most of them had negative attitudes about ANC. ANC (55.6%). There is a significant relationship between knowledge (p value: 0.000) and attitudes (p value: 0.000) with the completeness of ANC in adolescent pregnant women in the Pulomerak Health Center Working Area in 2021. It is expected that health workers will be more active in providing health education about high-risk pregnancies.